Cost and earnings of selected hatcheries in Panay and potential viability of using algal paste. - Eluriaga, Louie Marie T.; Esmilla, Macy G. (2015.)
The study determined the profitability of prawn and milkfish hatcheries operating in the Panay area and the possible viability of using algal paste as substitute to live microalgae. The result of the cost return analysis showed that both types of hatcheries operate profitability. Furthermore, this study required collaborator for the product testing. Collaboration, however, was only successful with the milkfish hatchery. On the other hand, potential viability of using algal paste for prawn hatcheries was determined using the preliminary data and by holding some assumptions. Consequently, survival rate of using algal paste was based on the laboratory experiment conducted by the College of Fisheries and Ocean Sciences. As for the absis of pricing for the algal paste, a shadow price and selling price was used. A cost comparison analysis of using algal paste and live microalgae showed that it was not economically viable for milkfish hatcehry to use the algal paste at both prices. For the prawn hatchery on the other hand, algal paste was economically viable to use only if the basis of pricing is the selling price. These results however, do not necessarily discount the fact that algal paste could still be used as substitute to live microalgae in milkfish hatchery especially if live microalgae culture has crashed.
Research Project (Undergraduate, Bachelor of Science in Economics) College of Arts and Sciences, University of the Philippines in the Visayas.
Keywords: Hatcheries -- Panay; Algal Paste